Si nanocrystals-based multilayers for luminescent and photovoltaic device applications *Project supported by the National Natural Science Foundation of China (Nos. 11774155, 11274155). (June 2018) - Lu, Peng; Li, Dongke; Cao, Yunqing; Xu, Jun; Chen, Kunji
Abstract: Low dimensional Si materials have attracted much attention because they can be developed in many kinds of new-generation nano-electronic and optoelectronic devices, among which Si nanocrystals-based multilayered material is one of the most promising candidates and has been extensively studied. By using multilayered structures, the size and distribution of nanocrystals as well as the barrier thickness between two adjacent Si nanocrystal layers can be well controlled, which is beneficial to the device applications. This paper presents an overview of the fabrication and device applications of Si nanocrystals, especially in luminescent and photovoltaic devices. We first introduce the fabrication methods of Si nanocrystals-based multilayers. Then, we systematically review the utilization of Si nanocrystals in luminescent and photovoltaic devices. Finally, some expectations for further development of the Si nanocrystals-based photonic and photovoltaic devices are proposed.